2014
DOI: 10.1099/mic.0.079913-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple native flavin reductases in camphor-metabolizing Pseudomonas putida NCIMB 10007: functional interaction with two-component diketocamphane monooxygenase isoenzymes

Abstract: Although they have been studied for nearly 50 years, the source of the FMNH 2 needed for effective biooxidation by the 2,5-and 3,6-diketocamphane monooxygenase (DKCMO) isoenzymes induced by the growth of Pseudomonas putida NCIMB 10007 (ATCC 17453) on camphor remains incompletely characterized. Prior studies have focussed exclusively on enzymes present in cells harvested during late-exponential-phase growth despite considerable circumstantial evidence that the flavin reductase (FR) component of these multicompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(47 citation statements)
references
References 56 publications
8
39
0
Order By: Relevance
“…The other inducible FNR-generating activity was located exclusively in relevant low MW fractions, and was only detectible in significant amounts from around the mid-log phase of camphor-dependent growth. Using previously described protocols [15], purification and subsequent characterisation confirmed that the principal protein in relevant low MW fractions corresponded to Fred, the chromosomally-coded 36 kDa NADH-dependent FNR-generating homodimeric enzyme isolated previously from camphor-grown P. putida NCIMB 10007 [5]. …”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The other inducible FNR-generating activity was located exclusively in relevant low MW fractions, and was only detectible in significant amounts from around the mid-log phase of camphor-dependent growth. Using previously described protocols [15], purification and subsequent characterisation confirmed that the principal protein in relevant low MW fractions corresponded to Fred, the chromosomally-coded 36 kDa NADH-dependent FNR-generating homodimeric enzyme isolated previously from camphor-grown P. putida NCIMB 10007 [5]. …”
Section: Resultsmentioning
confidence: 96%
“…One of these activities, located exclusively in the high MW fractions as confirmed by relevant native PAGE gels, promoted putidaredoxin-linked reduction of electron acceptors at the expense of NADH, and was induced in parallel with camphor exo -hydroxylase (Supplementary Figure S1). The principal protein present in the relevant samples was isolated (~51.0 kDa), analysed, and thereby confirmed to be identical to PdR [15], the monomeric protein product of the camA gene with a calculated molecular mass of 48.5 kDa [37,38]. The other inducible FNR-generating activity was located exclusively in relevant low MW fractions, and was only detectible in significant amounts from around the mid-log phase of camphor-dependent growth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations